Large Parotid Gland Lipoblastoma in a Teenager - Jandali, Danny; Heilingoetter, Ashley; Ghai, Ritu; Jeffe, Jill; Al-Khudari, Samer (Frontiers in Pediatrics, 2018)
Background: Lipoblastomas are rare benign neoplasms that arise from fetal white fat cells. They are typically found in children under the age of 3 and have been reported in the mediastinum, extremities, and infrequently in the head and neck. We present a rare case of a lipoblastoma arising from the parotid gland and the first known report of a parotid lipoblastoma in a teenager. Case Presentation: A 15-year-old male presented with a painless, slowly enlarging parotid mass and left facial swelling. A fine needle aspiration was non-diagnostic and initial MRI showed a 3.8 x 5.0 x 4.0 cm fatty lesion involving the superficial and deep lobes of the left parotid gland and masticator space with widening of the stylo-mandibular tunnel and thinning of the adjacent mandibular condyle. The patient was taken to the operating room, and the mass was excised under general anesthesia via a transcervical parotid approach with facial nerve monitoring. The most superficial aspect of the parotid bed was spared and with upper and lower divisions of the facial nerve preserved. The tumor, which primarily involved the deep lobe of the parotid, was entirely excised. Final pathology revealed a 5.2 cm lipoblastoma. The patient did well post-operatively with full function of the facial nerve and 20 months of follow up without evidence of recurrence. Conclusion: This is the first reported case of a lipoblastoma of the parotid gland in a teenager. Although a rare tumor, it should be considered in the differential diagnosis of a parotid mass in this population.